2018
DOI: 10.1186/s13148-018-0512-1
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and repressive H3K9 and H3K27 trimethylation in the promoter regions of PD-1, CTLA-4, TIM-3, LAG-3, TIGIT, and PD-L1 genes in human primary breast cancer

Abstract: BackgroundHigh expression of immune checkpoints in tumor microenvironment plays significant roles in inhibiting anti-tumor immunity, which is associated with poor prognosis and cancer progression. Major epigenetic modifications in both DNA and histone could be involved in upregulation of immune checkpoints in cancer.MethodsExpressions of different immune checkpoint genes and PD-L1 were assessed using qRT-PCR, and the underlying epigenetic modifications including CpG methylation and repressive histone abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 63 publications
8
96
0
Order By: Relevance
“…11 Recently, we have reported that in primary breast cancer (PBC), the transcriptomic expression of ICs including PD-1, CTLA-4, LAG-3 and TIM-3 was significantly higher in tumor tissue (TT) compared with normal tissue (NT). 12 Additionally, in CRC patients, ICs including PD-1, CTLA-4, TIM-3 and TIGIT and IC ligands including PD-L1 and galectin-9 were significantly upregulated in TT compared with NT. 13 Besides that, the promoter regions of PD-1, CTLA-4 and TIM-3 in PBC patients 12 and CTLA-4 and TIGIT in CRC patients, were significantly hypomethylated in TT, compared with NT.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…11 Recently, we have reported that in primary breast cancer (PBC), the transcriptomic expression of ICs including PD-1, CTLA-4, LAG-3 and TIM-3 was significantly higher in tumor tissue (TT) compared with normal tissue (NT). 12 Additionally, in CRC patients, ICs including PD-1, CTLA-4, TIM-3 and TIGIT and IC ligands including PD-L1 and galectin-9 were significantly upregulated in TT compared with NT. 13 Besides that, the promoter regions of PD-1, CTLA-4 and TIM-3 in PBC patients 12 and CTLA-4 and TIGIT in CRC patients, were significantly hypomethylated in TT, compared with NT.…”
Section: Introductionmentioning
confidence: 89%
“…12 Additionally, in CRC patients, ICs including PD-1, CTLA-4, TIM-3 and TIGIT and IC ligands including PD-L1 and galectin-9 were significantly upregulated in TT compared with NT. 13 Besides that, the promoter regions of PD-1, CTLA-4 and TIM-3 in PBC patients 12 and CTLA-4 and TIGIT in CRC patients, were significantly hypomethylated in TT, compared with NT. 13 Therefore, to check the molecular mechanism behind the expression of immune checkpoints and ligand in circulation, we investigated the transcriptomic expression analysis of various immune checkpoints/ligand, and also their promoter methylation pattern of both PBC and CRC patients compared to HD and tumor tissue.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Alternatively, promoter demethylation and distribution of repressive histones can work together to induce the upregulation of many genes in cancers [80]. Besides, it has been suggested that the enrichment of repressive histones, histone 3 lysine 9 trimethylation (H3K9me3) and H3K27me3 in the promoter regions along with CpG hypermethylation are the common epigenetic modifications in breast cancer [74]. Therefore, we hypothesized that TNFR2 gene might be highly expressed and demethylated in cancer models.…”
Section: Dna Demethylation and Immune Evasionmentioning
confidence: 98%
“…Although the critical role of TNFR2 in immune evasion of tumor cells, no study to date has been investigated on DNA methylation/demethylation in the TNFR2 gene in cancer subjects. Whereas there were significant findings have been reported recently in studies investigated on methylation/demethylation in several immune checkpoint genes including PD-1, PD-L1, CTLA-4, TIM-3, LAG-3 and TIGIT [73,74]. Demethylation and many mechanisms are part of the epigenetics field, which is considered as a gate for promising trends in cancer research in the current era.…”
Section: Dna Demethylation and Immune Evasionmentioning
confidence: 99%